Ploughing the wrong furrow: The costs of agricultural exceptionalism and the precautionary principle - Séan Rickard (Institute of Economic Affairs (IEA), 2016)
The precautionary principle provides non-farming interest groups with a pseudo-official means of influencing policy. The result is a drift towards overregulation and regulatory failures which are in conflict with the efficient working of the single market. Pressure groups have used a broad definition of the precautionary principle to bring about regulation in the areas of food standards, animal welfare and the environment which create deadweight costs and do not seem to be aligned with consumers' preferences. Official estimates suggest that compliance with existing agricultural regulations amount to 590 million a year in England, representing an increase in total operational costs by a little more than five per cent in England. This significantly underestimates the true cost of regulations because compliance costs do not take into account the longer term, and potentially much larger, costs arising from the impact on competitiveness and the affordability of food. Researchers estimate that overall crop yields would be around half their current levels without the use of crop protection products. Further restrictions on pesticide use would reduce crop yields across the EU and substantially increase the price of food. If all food had to be grown organically, yields for wheat, beans and potatoes would fall by 49 per cent, 26 per cent and 44 per cent respectively, leading to prices rising by 69 per cent, 53 per cent and 192 per cent respectively. Allowing for the increased costs of feedstuffs, farm-gate prices for meat and dairy products would average out around 25 per cent higher. In the extreme scenario in which all pesticides are banned, the UK food chain would be faced with additional raw material costs of some 7.5 billion per year. It is not suggested that all synthetic plant protection products are likely to banned. However, as current EU policy is directed towards significant reductions in synthetic crop protection products, these estimates serve to indicate that Defra's current estimate of 590 million for the total annual cost of complying with existing regulations is a significant underestimate of the potential costs. It is unlikely that the benefits of the current regulatory burden outweigh the costs. The EU's precautionary approach discourages the development of technologies with even a low, theoretical probability of harm despite offering the likelihood of faster agricultural productivity growth. Attempts by authorities to demonstrate the positive net benefits of mandatory regulations are flawed because they do not take in the adverse effects for longer term technological advance and farm level operational efficiencies. The costs in terms of efficiency, competitiveness and living standards are likely to be high.
Keywords: 330